Association between TSH-Receptor Autoimmunity, Hyperthyroidism, Goitre, and Orbitopathy in 208 Patients Included in the Remission Induction and Sustenance in Graves' Disease Study. (18th February 2014) - Laurberg, Peter; Nygaard, Birte; Andersen, Stig; Carlé, Allan; Karmisholt, Jesper; Krejbjerg, Anne; Pedersen, Inge Bülow; Andersen, Stine Linding
Abstract : Background . Graves' disease may have a number of clinical manifestations with varying degrees of activity that may not always run in parallel. Objectives . To study associations between serum levels of TSH-receptor autoantibodies and the three main manifestations of Graves' disease (hyperthyroidism, goiter, and presence of orbitopathy) at the time of diagnosis of hyperthyroidism. Methods . We describe a cohort of 208 patients with newly diagnosed Graves' hyperthyroidism. Patients were enrolled in a multiphase study of antithyroid drug therapy of Graves' hyperthyroidism, entitled "Remission Induction and Sustenance in Graves' Disease (RISG)." Patients were systematically tested for degree of biochemical hyperthyroidism, enlarged thyroid volume by ultrasonography, and the presence of orbitopathy. Results . Positive correlations were found between the levels of TSH-receptor autoantibodies in serum and the three manifestations of Graves' disease: severeness of hyperthyroidism, presence of enlarged thyroid, and presence of orbitopathy, as well as between the different types of manifestations. Only around half of patients had enlarged thyroid gland at the time of diagnosis of hyperthyroidism, whereas 25–30% had orbitopathy. Conclusions . A positive but rather weak correlation was found between TSH-receptor antibodies in serum and the major clinical manifestation of Graves' disease. Only half of the patients had an enlarged thyroid gland at the time of diagnosis.